The Influence of Member Perceptions, Service Quality, and Trust on Member Loyalty by Intervening Organizational Image (Case Study of the IAI Organization in Tangerang Regency) - Mulyani, Kartika; Brabo, Nora Andira; Iswati, Heni (International Journal of Finance Research, 2024)
This research aims to analyze the influence of member perceptions, service quality, and trust on member loyalty by intervening with the organizational image of the Indonesian Pharmacists Association (IAI) in Tangerang Regency. This research used a survey method with 315 people using the Simple Random Sampling technique. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique uses the software program application using multiple linear regression analysis and path analysis. The research results provide conclusions: (1) Members' perceptions have a positive and significant effect on the organization's image; (2) Service quality has a positive and significant effect on the organization's image; (3) Member trust has a positive and significant effect on the organization's image; (4) perception, quality of service, and trust together have a positive and significant effect on the organization's image; (5) Member perceptions have a positive and significant effect on member loyalty; (6) Service quality has a positive and significant effect on member loyalty; (7) Trust has a positive but not significant effect on member loyalty; (8) Perception, service quality and trust simultaneously influence member loyalty; (9) Perception, service quality and trust simultaneously influence member loyalty through organizational image as an intervening variable